Development of Simple Analytical Method for B-Group Vitamins in Nutritional Products: Enzymatic Digestion and UPLC-MS/MS Quantification - Quang Huy Nguyen; Anh Quoc Hoang; Thi My Hanh Truong; Thi Diu Dinh; Thi Thuy Le; Thi Huyen Trang Luu; Viet Chien Dinh; Thi Minh Thu Nguyen; Thi Trang Vu; Thi Anh Huong Nguyen (Journal of Analytical Methods in Chemistry)
A method for the simultaneous determination of seven B-group vitamers including thiamine, riboflavin, nicotinamide, niacin, pyridoxine, pyridoxal, and pyridoxamine in nutritional products by using enzymatic digestion followed by LC-MS/MS quantification was studied. The LC-MS/MS conditions such as MS transitions, mobile phase programs, and ammonium formate buffer concentrations, and sample treatment procedures (e.g., concentrations of buffer solution, digestion temperature, and digestion time) were investigated. The analytical method performance was evaluated by multiple criteria such as selectivity, linearity, detection and quantification limits, repeatability, reproducibility, and recovery by using real sample matrices. The validated method was successfully applied to analyze vitamin B concentrations in different nutritional products like ultra-heat-treated milk, powdered milk, and nutritional powder. Vitamin B concentrations varied over a wide range from lower than detection limits to about 9000 µg/100 g, depending on vitamin groups, compound forms, and sample types. The measured concentrations of B-group vitamins in our samples were generally in good agreement with values of label claims.